2019
DOI: 10.1164/rccm.201807-1345oc
|View full text |Cite
|
Sign up to set email alerts
|

Club Cell Secretory Protein Deficiency Leads to Altered Lung Function

Abstract: Rationale: CC16 (club cell secretory protein-16), a member of the secretoglobin family, is one of the most abundant proteins in normal airway secretions and has been described as a serum biomarker for obstructive lung diseases. Objectives: To determine whether low CC16 is a marker for airway pathology or is implicated in the pathophysiology of progressive airway damage in these conditions. Methods: Using human data from the birth cohort of the Tucson Children's Respiratory Study, we examined the relation of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 57 publications
(71 reference statements)
6
58
0
Order By: Relevance
“…In our study, we observed that decreased plasma CC10 levels were associated with air ow limitation and damaged lung functions among asthmatic patients. Concurrently, we found a negatively correlation between plasma CC10 levels and bronchial hyperresponsiveness in asthmatic patients, which was in line with a recently report showing that low serum CC16 enhanced airway hyperresponsiveness to methacholine challenge in adults [29] . This scenario demonstrated that CC10 alleviated airway obstruction and hyperresponsiveness as a result of inhibition of Th-2 in ammation in asthma.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we observed that decreased plasma CC10 levels were associated with air ow limitation and damaged lung functions among asthmatic patients. Concurrently, we found a negatively correlation between plasma CC10 levels and bronchial hyperresponsiveness in asthmatic patients, which was in line with a recently report showing that low serum CC16 enhanced airway hyperresponsiveness to methacholine challenge in adults [29] . This scenario demonstrated that CC10 alleviated airway obstruction and hyperresponsiveness as a result of inhibition of Th-2 in ammation in asthma.…”
Section: Discussionsupporting
confidence: 92%
“…Decreased levels of circulating CC16 are prospectively associated with lung cancer mortality, COPD development and lung function deficits in both children and adults (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Club cell secretory protein 16 (CCSP16) is produced predominantly by club cells and non-ciliated epithelial cells in the distal airways and is readily detectable in the peripheral circulation [65]. Mounting evidence suggests that this protein is critical in mediating anti-inflammatory and anti-oxidant functions within the lung and, by virtue of these activities, may protect against development of obstructive lung diseases [66].…”
Section: 2mentioning
confidence: 99%
“…BAL levels of CCSP16 correlated with epithelial detachment suggesting its possible role of in the remodeling process. Zhai and colleagues [66] using human data from a birth cohort, suggested that low circulating CCSP16 levels were not only a biomarker of airway pathology but may be implicated in the pathophysiology of the progressive airway damage that characterize obstructive lung diseases. Moreover, urinary CCSP16 may be a useful tool or biomarker for studying asthma and the integrity of the alveolar epithelium in children with lung injury [69].Emerging biomarkers:…”
Section: 2mentioning
confidence: 99%